2007
DOI: 10.1063/1.2746240
|View full text |Cite
|
Sign up to set email alerts
|

Electronically induced modification of thin layers on surfaces

Abstract: Interactions of thermally and electronically stimulated reactions in thin layers on surfaces are investigated. For self-assembled monolayers, thermal activation promotes many processes primarily induced by electronic excitations. We demonstrate that the film temperature is an important parameter for steering these reactions towards different final products. Using chemisorbed water on Ru(001) as an example, we investigate how the products of an irradiation induced reaction catalyze thermally stimulated dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
(66 reference statements)
2
1
0
Order By: Relevance
“…A very similar observation has been reported by Clay et al and Bauer et al when studying the peculiarities of water thermal desorption on Ru(0001). In their studies, they identified efficient H-atom transfer to nearby surface-O atoms as the main source of temporary dissociation of H 2 O.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A very similar observation has been reported by Clay et al and Bauer et al when studying the peculiarities of water thermal desorption on Ru(0001). In their studies, they identified efficient H-atom transfer to nearby surface-O atoms as the main source of temporary dissociation of H 2 O.…”
Section: Resultssupporting
confidence: 88%
“…Experimentally, the promotion of methanol OsH bond breaking by surface-O atoms is frequently observed on Cu, Ag, Pt, and Pd substrates. 9,10,14,21, 22,[30][31][32][33] A very similar observation has been reported by Clay et al 49 and Bauer et al 50 when studying the peculiarities of water thermal desorption on Ru(0001). In their studies, they identified efficient H-atom transfer to nearby surface-O atoms as the main source of temporary dissociation of H 2 O.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation